Acute Normobaric Hypoxia Increases Post-exercise Lipid Oxidation in Healthy Males - Kelly, Liam P.; Basset, Fabien A. (Frontiers in Physiology, 2017)
The primary objective of the current study was to determine the effect of moderate normobaric hypoxia exposure during constant load cycling on post-exercise energy metabolism recorded in normoxia. Indirect calorimetry was used to examine whole body substrate oxidation before, during, 40-60 min post, and 22 hrs after performing 60 min of cycling exercise at two different fractions of inspired oxygen (FIO2): (i) FIO2 = 0.2091 (normoxia) and (ii) FIO2 = 0.15 (hypoxia). Seven active healthy male participants (26 ± 4 years of age) completed both experimental trials in randomized order with a 7-day washout period to avoid carryover effects between conditions. Resting energy expenditure was initially elevated following cycling exercise in normoxia and hypoxia (Δ 0.14 ± 0.05, kcal min-1, p = 0.037; Δ 0.19 ± 0.03 kcal min-1, p < 0.001, respectively), but returned to baseline levels the next morning in both conditions. Although the same absolute workload was used in both environmental conditions (157 ± 10 W), a shift in resting substrate oxidation occurred after exercise performed in hypoxia while post-exercise measurements were similar to baseline after cycling exercise in normoxia. The additional metabolic stress of hypoxia exposure was sufficient to increase the rate of lipid oxidation (Δ 42 ± 11 mg min-1, p = 0.019) and tended to suppress carbohydrate oxidation (Δ -55 ± 26 mg min-1, p = 0.076) 40-60 min post-exercise. This shift in substrate oxidation persisted the next morning, where lipid oxidation remained elevated (Δ 9 ± 3 mg min-1, p = 0.0357) and carbohydrate oxidation was suppressed (Δ -22 ± 6 mg min-1, p = 0.019). In conclusion, prior exercise performed under moderate normobaric hypoxia alters post-exercise energy metabolism. This is an important consideration when evaluating the metabolic consequences of hypoxia exposure during prolonged exercise, and future studies should evaluate its role in the beneficial effects of intermittent hypoxia training observed in persons with obesity and insulin resistance.